2018
DOI: 10.1002/ajb2.1083
|View full text |Cite
|
Sign up to set email alerts
|

Finding the seasons in tree ring stable isotope ratios

Abstract: A m e r i c a n J o u r n a l o f B o t a ny 820 • Tree ring seasons-Monson et al. • Volume 105,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…Thus, the temporal lag between volumetric growth and carbon allocated to cellulose observed here is consistent with data from the global analysis by Cuny et al () (Figure ). The result is also consistent with recent work on the isotopic composition of cellulose from other conifers in the southwestern United States, which found that the isotopic ratio of cellulose within a tree‐ring correlated most strongly with climate a month or more after the cells formed (Monson et al, ; Szejner et al, ). Taken together, the comparison of the modeled transpiration and photosynthesis with sap flux, satellite GPP, and dendrometry data, all indicate that the modeled seasonal cycle in cellulose is approximately accurate.…”
Section: Resultssupporting
confidence: 91%
“…Thus, the temporal lag between volumetric growth and carbon allocated to cellulose observed here is consistent with data from the global analysis by Cuny et al () (Figure ). The result is also consistent with recent work on the isotopic composition of cellulose from other conifers in the southwestern United States, which found that the isotopic ratio of cellulose within a tree‐ring correlated most strongly with climate a month or more after the cells formed (Monson et al, ; Szejner et al, ). Taken together, the comparison of the modeled transpiration and photosynthesis with sap flux, satellite GPP, and dendrometry data, all indicate that the modeled seasonal cycle in cellulose is approximately accurate.…”
Section: Resultssupporting
confidence: 91%
“…Fine‐scale sampling of secondary growth, isotopic composition and wood anatomical features has enabled the study of intra‐seasonal tree growth dynamics in response to environmental and ecophysiological processes (Helle & Schleser, ; Gessler et al , ; Treydte et al , ; Sargeant & Singer, ; Cuny et al , ; Helliker et al , ; Monson et al , ), and this fine‐scale sampling approach has led to a re‐examination of our fundamental understanding of how environmental factors are recorded in δ 18 O of cellulose (δ 18 O cell ) (Roden et al , ; Cheesman & Cernusak, ). The intra‐annual record of δ 18 O cell can be decoupled from the climate variables under which the cambial cells are produced, and this decoupling can be related to temporal lags in xylogenesis and post‐carboxylation processes (Lévesque et al , ; Belmecheri et al , ; Nabeshima et al , ; Szejner et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…It has long been known that vegetation response to environmental variability is revealed by tree rings (e.g., Monson et al 2018) and that a careful study of their anatomy provides critical insight into plant physiological responses to climate. Szejner et al (2021) assess stable isotopes in tree rings to reveal that trees near the arid range limit herald recent megadroughts in the southwestern U.S. Heilman et al (2021) use tree rings to find that plant water use efficiency has increased across the savanna-forest ecotone in the Midwestern U.S., but also show that growth has not and is now less sensitive to precipitation variability, especially in trees growing in open canopy microclimates.…”
Section: Tree-ring Researchmentioning
confidence: 99%